A review of the Pliocene bandicoots of Australia, and descriptions of new genus and species. Issue 5 (3rd September 2017) - Travouillon, Kenny J.; Louys, Julien; Price, Gilbert J.; Archer, Michael; Hand, Suzanne J.; Muirhead, Jeanette
ABSTRACT: The Pliocene fossil record of Australia has revealed the oldest known occurrences of modern peramelemorphian (bandicoot and bilbies) genera such as Perameles, cf. Peroryctes, and Chaeropus . Recent phylogenetic analyses based on morphology have questioned the previously accepted understanding about generic relationships of some of these Pliocene taxa. These doubts limit our ability to develop independent divergence models based on molecular data because they depend on fossil records in order to calibrate minimum rates of change. Hence, there is a need to critically review the Pliocene fossil record. To this end, we have examined Pliocene specimens of peramelemorphians in museum collections across Australia and performed a comprehensive phylogenetic analysis based on dental and cranial morphology to review and accordingly revise subfamilial taxonomy. As part of this revision, we describe here two new species, one from the Chinchilla Local Fauna (LF) in Queensland ( Perameles wilkinsonorum, sp. nov.) and one from both the Big Sink LF in the Wellington Caves area and the Bow LF in New South Wales ( Silvicultor karae, gen. et sp. nov.). We reassign the two ' Peroryctes ' species from Hamilton LF, Victoria, to a new genus ( Silvicultor ). We summarize the distribution of peramelemorphians during the Pliocene and show how climate change appears to have shaped their subsequent Quaternary distribution. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Travouillon, K. J., J. Louys, G. J. Price, M. Archer, S. J. Hand, and J. Muirhead. 2017. A review of the Pliocene bandicoots of Australia, and descriptions of new genus and species. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1360894.